Do you name the mystery? (Journal of Parents and Teachers, 2014)
The following article deals with the mystery. It talks about this concept from its religious conception, to its multiple perspectives such as love, sense or mystery’s function. In addition, it delves into the false mystery from a reflective perspective about what the origin and the function are. Everything focuses on naming to that mystery in which many occasions it appears.
Keywords: mystery; origin; sense; function; mystery’s name; mystery’s perspectives.